Concepts and Methods of Tadabbur al-Qur'an for Early Childhood: A Review of the Book Tadabbur al-Qur’an for Kids - Azkian Nur, Zulfi; Sulthoni, Akhmad (JIA (Jurnal Ilmu Agama), 2024)
Islam places great importance on the education of children starting from an early age. If children lack education at the beginning of their lives, some of them will grow up with corrupt morals, like lying, envy, stealing, criticizing, and interfering in other people's affairs. The Qur'anic surah that alludes to the importance of the existence of children themselves is QS. al-Kahf verse 46, Allah says: “Treasures and children are ornaments in the life of the world”. This study aims to discuss the concept and method of tadabbur al-Qur'an through analyzing the work of the Ummul Qura' editorial team, namely the book Tadabbur Al-Qur’an for Kids. By using qualitative methodology, literature study, this research focuses on two main aspects: the understanding of the editorial team of Ummul Qura' about the concept and method of tadabbur al-Qur'an for early childhood, and how it is implemented in everyday life. The results showed that the editorial team of Ummul Qura' was able to provide solutions for early childhood education by presenting an applicable and meaningful understanding, including presenting convenience for children in tadabbur al-Qur'an, making it easy to memorize the Qur'an, presenting the translation of each verse, introducing the naming of the surah of the Qur'an, tadabbur and understanding the essence of the Qur'an's science, a guide to practicing the contents of the Qur'an, complete references, inviting children to dive further, and providing motivation to become experts in the Qur'an.